Multiplikasi Tunas Tetrastigma rafflesiae Miq. pada Media Tanam Murashige-Skoog dengan Penambahan 6-Benzylaminopurine dan 1-Naphtaleneacetic Acid secara In Vitro - Ridha Permata Sari; - Suwirmen; M. Idris (Jurnal Biologi Universitas Andalas, 2013)
The study about in vitro shoot multiplication of Tetrastigma rafflesiae miq. on murashige-skoog media with addition of 6-Benzylaminopurine and 1-Naphtaleneacetic Acid had purpose to determine physiological responses of Tetrastigma rafflesiae nodes with addition of 6-Benzylaminopurine (BAP) and 1-Naphtaleneacetic Acid (NAA) in several concentrations on shoot multiplication stages. This experiment used randomised complete design in 11 treatments and three replications. The treatment were the addition of BAP (1.0-5.0 mg/l) and its combination with NAA (0.1 mg/l) on MS medium. The results showed that nodus successfully producing shoot and callus. The addition of BAP was more effective than its combination with NAA in shoot multiplication. MS medium with addition of 2.0-4.0 mg / l BAP showed a better media for shoot multiplication (2.3-2.7 shoot each explant). Generally, MS media with combination of BAP and NAA produced a higher shoot although it did not significantly differed with BAP treatments. The result indicated that addition of BAP in in vitro medias have a high possibility of success for shoot multiplications in Rafflesia’s host plant conservation. Keywords: 1-Naphtaleneacetic Acid, 6-Benzylaminopurine, Murashige-Skoog media, Shoot multiplication.